2008
DOI: 10.3998/ark.5550190.0010.306
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic decomposition of glycosides in aqueous acids

Abstract: A review is presented that collects the experimental results published on the acid catalyzed hydrolysis of alkyl and aryl pyranosides and furanosides over the last three decades. In aqueous acid, alkyl furanosides and pyranosides are hydrolysed via an oxocarbenium intermediate, which may be formed from the protonated substrate either by an exocyclic or endocyclic C-O bond cleavage. Both mechanisms lead eventually to the same products. Various methods have been used to distinguish between the pathways, and a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is known that the cleavage of the glycosidic bond of alkyl furanosides and pyranosides could be conducted under acidic conditions, specifically furanosides are less stable against acid and hydrolysis of furanosides is generally faster than reactions of pyranosides. 15,16 Considering that the removal of the p-methoxybenzyl group could also be achieved under strong acidic conditions, simultaneous deprotection of butyl and p-methoxybenzyl groups was attempted by direct treatment of 28b with 30% trifluoroacetic acid solution which was unsuccessful and a complex mixture of decomposed products was obtained. In the subsequent investigation, it was found that the glycosidic bond of 28b is less stable under mild acidic conditions, which facilitated selective removal of the butyl group.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the cleavage of the glycosidic bond of alkyl furanosides and pyranosides could be conducted under acidic conditions, specifically furanosides are less stable against acid and hydrolysis of furanosides is generally faster than reactions of pyranosides. 15,16 Considering that the removal of the p-methoxybenzyl group could also be achieved under strong acidic conditions, simultaneous deprotection of butyl and p-methoxybenzyl groups was attempted by direct treatment of 28b with 30% trifluoroacetic acid solution which was unsuccessful and a complex mixture of decomposed products was obtained. In the subsequent investigation, it was found that the glycosidic bond of 28b is less stable under mild acidic conditions, which facilitated selective removal of the butyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Simply comparing the rate of hydrolysis of acetal trans - 6 to that of isovaleraldehyde acetal 12 shows that an alkoxy group can accelerate hydrolysis compared to that of an acyclic acetal by nearly one order of magnitude. Because acetal hydrolysis involves reversible protonation followed by rate-limiting ionization, , the cationic intermediate formed from acetal trans - 6 must be stabilized by the alkoxy group four atoms away. It cannot be differentiated whether this effect results from electrostatic stabilization by the benzyloxy group, as suggested for hydrolysis of galactose (eq ), , or whether a new covalent bond is formed during ionization, resulting in formation of an onium ion intermediate (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also unlikely that α particles are held together by other glycosidic linkages because the kinetics for the acid hydrolysis of α-(1→2) and α-(1→3) are very similar to that of α-(1→4), and the acid hydrolysis of the anomeric β glycosidic linkages, while more thermodynamically favorable, occurs at slower rates than glycosidic linkages. , …”
Section: Resultsmentioning
confidence: 99%
“…45 It is also unlikely that α particles are held together by other glycosidic linkages because the kinetics for the acid hydrolysis of α-(1→2) and α-(1→3) are very similar to that of α-(1→4), and the acid hydrolysis of the anomeric β glycosidic linkages, while more thermodynamically favorable, occurs at slower rates than glycosidic linkages. 43,46 It is well-established that peptide hydrolysis is catalyzed by acid, 47 and whereas complete hydrolysis of proteins into single amino acids requires very low pH values at high temperatures, partial hydrolysis occurs under much milder conditions 48 and even occurs spontaneously in water at neutral pH. 49 The firstorder rate coefficient for the hydrolysis of internal peptide bonds (exemplified using acetylglycylglycine N-methylamide) under neutral conditions has been studied over a range of temperatures.…”
Section: Biomacromoleculesmentioning
confidence: 99%